2019
DOI: 10.1093/mnras/stz1801
|View full text |Cite
|
Sign up to set email alerts
|

Correlated timing noise and high-precision pulsar timing: measuring frequency second derivatives as an example

Abstract: We investigate the impact of noise processes on high-precision pulsar timing. Our analysis focuses on the measurability of the second spin frequency derivative ν. This ν can be induced by several factors including the radial velocity of a pulsar. We use Bayesian methods to model the pulsar times-of-arrival in the presence of red timing noise and dispersion measure variations, modelling the noise processes as power laws. Using simulated times-of-arrival that both include red noise, dispersion measure variations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…The above estimate is for an offset dipole; if quadrupole or higher multipole components dominate the spin-down luminosity, as could be the case for PSR J0030+0451, then the expression for the kick velocity would change. It must be noted that measuring the 3D velocity of a pulsar is difficult because the radial component of the velocity is hard to disentangle from the intrinsic second time derivative of pulsar period P (see the extensive discussion in Liu et al 2018Liu et al , 2019. Even for such a well-timed pulsar as PSR J0030+0451, the radial velocity is at present unknown.…”
Section: Pulsar Space Velocitiesmentioning
confidence: 99%
“…The above estimate is for an offset dipole; if quadrupole or higher multipole components dominate the spin-down luminosity, as could be the case for PSR J0030+0451, then the expression for the kick velocity would change. It must be noted that measuring the 3D velocity of a pulsar is difficult because the radial component of the velocity is hard to disentangle from the intrinsic second time derivative of pulsar period P (see the extensive discussion in Liu et al 2018Liu et al , 2019. Even for such a well-timed pulsar as PSR J0030+0451, the radial velocity is at present unknown.…”
Section: Pulsar Space Velocitiesmentioning
confidence: 99%
“…Also, for a given pulsar, different sections of the data span can have different values of ν, often changing from positive to negative values. Liu et al (2019) investigated the detectability of ν in the presence of red noise for a sample of millisecond pulsars. Using simulations, it was found that a non-zero ν could be recovered when data spans are sufficiently long.…”
Section: Braking Indicesmentioning
confidence: 99%
“…We end up with 158 pulsars satisfying these conditions. We take a nominal v rad = 50 km/s, like Liu et al (2019), for the pulsars except for J1024−0719 and JJ1903+0327 whose v rad is known to be 185(4) km/s and 42.1(25) km/s respectively (Liu et al 2018). We get that n varies from −4.2 × 10 7 to 7.7 × 10 7 .…”
Section: Intrinsic Spin Frequency Second Derivative and The Braking I...mentioning
confidence: 99%